Pelatihan Penggunaan Aplikasi Zoom Untuk Pembelajaran Daring di MTs Muhammadiyah 02 Pekanbaru - Harun Mukhtar; Rahmad Firdaus; Diah Angraini Putri; Febby Apri Wenando; Mitra Unik; Januar Al Amien; Evans Fuad; Soni soni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
With the COVID-19 pandemic, human activities have been disrupted, including the learning process in the education sector. The government issued a policy that learning is online. The online learning method requires to master the use of technology and it is still considered new by most teachers, that’s why this community service is carried out. This activity is intended for all teachers and teaching staff at MTs Muhammadiyah 02 Pekanbaru and Activities are carried out with three processes, namely preparation, implementation, and evaluation. The preparation stage is carried out by meeting with the school to determine the topic, schedule, and timing. The implementation stage is carried out by presenting and practicing the use of the Zoom application directly. The evaluation stage is carried out by helping to receive complaints about the use of applications from participants after the activity is carried out. The results of community service activity can increase the ability to use the Zoom application so that the online learning process becomes effective and maximized.